Adjunctive corticosteroid treatment for organizing pneumonia in COVID-19 patients with persistent respiratory failure. (October 2021) - Segala, Francesco Vladimiro; Sgalla, Giacomo; Salvati, Federica; Berardini, Ludovica; Negri, Marcantonio; Nardella, Elisabetta; Potenza, Annalisa; Murri, Rita; Fantoni, Massimo
Abstract: Since the beginning of COVID-19 pandemic, clinical, radiological and histopathological features consistent with viral-induced organizing pneumonia (OP) have been reported as hallmark characteristics of the disease. Here, we describe the case of ten patients with severe COVID-19 pneumonia treated with methylprednisolone 1mg/kg for showing clinical and radiological features suggestive of OP at least 20 days after symptom onset and despite standard treatment for COVID-19.